A Clinician's Guide to Cancer-Derived Exosomes: Immune Interactions and Therapeutic Implications - Knox, Matthew C.; Ni, Jie; Bece, Andrej; Bucci, Joseph; Chin, Yaw; Graham, Peter H.; Li, Yong (Frontiers in Immunology, 2020)
Understanding the role of immunity in the regulation of cancer growth continues to rapidly increase. This is fuelled by impressive results yielded in recent years by immune checkpoint inhibitors, which block regulatory pathways to increase immune-mediated cancer destruction. Exosomes are cell-secreted membranous nanoscale vesicles that play important roles in regulating physiological and pathophysiological processes. Cancer-derived exosomes (CDEXs) and their biologically-active cargos have been proven to have varied effects in malignant progression, including the promotion of angiogenesis, metastasis, and favourable microenvironment modification. More recently, there is an increasing appreciation of their role in immune evasion. In addition to CDEXs, there are immune-derived exosomes that facilitate communication between immune cells in the non-malignant setting. Investigation of cancer-mediated mechanisms behind interruption or modification of these normal exosomal pathways may provide a further understanding of how malignant immune evasion is accomplished. Accumulating evidence indicates that immune-active CDEXs also have the potential to impact clinical oncological management. Whilst immune checkpoint inhibitors have well established pharmacologically-targeted pathways involving the immune system, other widely used treatments such as radiation and cytotoxic chemotherapies do not. Thus, investigating exosomes in immunotherapy is important for the development of next-generation combination therapies. In this article, we review the ways in which CDEXs impact individual immune cell types and how this contributes to the development of immune evasion. We discuss the relevance of lymphocytes and myeloid-lineage cells (including dendritic cells) in the control of malignancy. In addition, we highlight the ways that CDEXs and their immune effects can impact current cancer therapies and the resulting clinical implications.